Glórias, conquistas, perdas e disputas: as muitas máscaras dos carnavais de rua em Belo Horizonte(1899 1936) - Hilario Figueiredo Pereira Filho (2006)
This work studies the carnival of the city of Belo Horizonte in the period 1899-1936. Although there were supposedly elegant and civilized discourses about carnival at the newborn capital of Minas Gerais, one could notice the existence of a wide range of cultural expressions on these street festivities. Hence, the research focus on the oppositions, tensions and the agreements involving the desired model of carnival and the multiplicity of meanings that emerged in the party. However, further than simply pointing out an antagonism of dichotomist perspectives,our proposal aims to notice how these diverse points-of-view about the festivities were built and constantly re-signified by several social actors: members of carnival clubs, government representatives, chroniclers, writers, loafers, students, and works were some examples ofactors that added new meanings of the symbolic dynamics of carnival. These meanings traversed Belo Horizontes quotidian, revelation its political, social and cultural life.